A Review of Geomechanical Risk Management in Well Planning: Global Practices and Lessons from the Niger Delta - Joshua Emeka Ozor; Oludayo Sofoluwe; Dazok Donald Jambol (International Journal of Scientific Research in Civil Engineering, 2021)
Geomechanical risk management has become an essential pillar of modern well planning, particularly in geologically complex basins such as the Niger Delta. This paper presents a comprehensive review of global best practices in geomechanical modeling, hazard mitigation, and decision support, emphasizing their relevance and adaptability to regional operations. Beginning with a foundational overview of subsurface stress regimes, rock failure mechanisms, and data requirements, the study explores how advanced geomechanical approaches are applied across diverse petroleum provinces—including North America, the North Sea, the Middle East, and Asia-Pacific. These regions demonstrate the value of integrated workflows, real-time monitoring, and alignment with international standards. Drawing on operational experiences from the Niger Delta, the paper highlights recurring challenges such as wellbore instability, data scarcity, and underestimation of pressure regimes. It also identifies emerging practices and opportunities for local capacity building and model customization. Ultimately, this review underscores the strategic importance of embedding geomechanical intelligence into planning, governance, and continuous improvement frameworks to reduce drilling risks, enhance well integrity, and improve cost efficiency in complex geologic settings.